If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X=-36+3X
We move all terms to the left:
X-(-36+3X)=0
We add all the numbers together, and all the variables
X-(3X-36)=0
We get rid of parentheses
X-3X+36=0
We add all the numbers together, and all the variables
-2X+36=0
We move all terms containing X to the left, all other terms to the right
-2X=-36
X=-36/-2
X=+18
| -2.5x-7.7=-2.8-2.9x | | Y=15x1+22.50 | | 8(x-4)=-40 | | X(8x+2)=0 | | 2x+9x+15=48 | | (3x+5)*(3x+5)=7 | | 84÷n=21 | | K^2-6k-90=9 | | y+4=2y-31 | | -2(5x-7)=-6 | | 2x2+5x−3=2xx+192 | | 7y-3=2y+1 | | 5/12+1/12(x-1)=3/4 | | n/5+0.6=2 | | a-27=-18 | | (3y-2)^2=16 | | 4x+4=2x+-5 | | 17=16k | | 7y+12=4y+27 | | x2−12x+35=(x−7)(x+5) | | 5x-10-3x=2x+20-3x | | -18=5-(6k-19 | | -4n+6=16 | | 2a-18=3a+27 | | −5(p+3/5)=−4 | | 5t^2-18t-35=0 | | |7x+3|+2=33 | | -x+5x+60=-12 | | 42-x3=15 | | 2x-4(-3)=-5+2x-15 | | X/10=x/11-3 | | x(9x^2-6x+1)=0 |